A qualitative study on reasons for early removal of Implanon among users in Arba Minch town, Gamo Goffa zone, South Ethiopia: a phenomenological approach - Mesfin Mamo Utaile; Mesfin Kote Debere; Etsehiwot Tilahun Nida; Dube Jara Boneya; Amsale Tekle Ergano (BMC, 2020)
Abstract Background Implanon is one of the cost - effective long acting reversible contraceptive methods used for spacing and limiting births in Ethiopia. Despite the scaling up initiative undertaken by the Ethiopian Government, Implanon uptake is very low compared to short acting contraceptive methods. There is low utilization of Implanon with high level of discontinuation in Ethiopia. Therefore, this study was conducted to explore the reasons for early removal of Implanon among users in Arba Minch town, South Ethiopia. Methods A community-based qualitative exploratory study using phenomenological approach was conducted. In-depth and key informant interviews were used to collect data from April 20-27, 2018 in Arba Minch town. Convenient sampling was employed to recruit participants from the households of targeted villages. A total of 10 in-depth interviews with women who recently removed Implanon and 5 key informant interviews with health extension workers were conducted. The sample size was determined based on the concept of saturation. The collected data were analyzed using thematic content analysis technique. Data coding and analysis were facilitated by using Open code version 4.0 software. Results This study revealed that majority of participants were able to mention at least three types of contraceptive methods available in the nearby health facilities. The study underlined that side effect of the method, husband opposition, seeking more children, and method failure were the common reasons for early removal of Implanon, in which side effect of the method was the main reason. Among various forms of side effects of Implanon identified by users, heavy and irregular bleeding was mentioned as the most frequently occurring side effect. Conclusion Our result indicated that heavy and irregular bleeding was the main reason for early removal of Implanon. Therefore it suggests improvement in the service delivery system. Improving client's education and counseling service program could contribute much to avoid unreasonable and untimely removal of Implanon.